ChemInform Abstract: ′Interrupted′ Diazotization of 3‐Aminoindoles and 3‐Aminopyrroles. Issue 10 (March 2015) - Parrino, Barbara; Spano, Virginia; Carbone, Anna; Montalbano, Alessandra; Barraja, Paola; Matyus, Peter; Cirrincione, Girolamo; Diana, Patrizia
Abstract The interrupted diazotization of 3‐aminoindoles and 3‐aminopyrroles, achieved by quenching with cold water immediately after addition of nitrite, leads to diazonium species with nitrate as counter ion.